Morphological study on the Danger Zone of the mesiobuccal canal prepared by three nickel-titanium rotary systems using three-dimensional printed mandibular first molars - LIU Yuqing, DAI Jiayun, ZHOU Duo, WANG Xingyang, XU Fulu, WANG Juan (Kouqiang yixue, 2025)
Objective To compare the effects of three nickel-titanium file systems, ProTaper Next, TruNatomy, and VDW. ROTATE, on the morphology of the Danger Zone of the mesial buccal root of mandibular first molar after root canal preparation using Micro-CT and 3D printing technology. Methods 3D-printed mandibular first molars were selected and designed for purpose. They were randomly divided into three groups according to the used NiTi files(n=20). Micro-CT was used to scan the cross-sectional images of the Danger Zone 2 mm below the furcation of the mesial buccal root before and after root canal preparation. The changes in the root canal wall thickness, root canal volume, surface area, cross-sectional area, and root canal transportation in the Danger Zone were observed. Statistical analysis was performed using one-way ANOVA(P<0.05). Results Statistically significant differences were observed before and after root canal preparation in the Danger Zone among the three groups(P<0.05). Among the three groups, the PTN files caused the largest change before and after preparation, followed by VDW files, and the TRU files had the smallest change. Conclusion The study highlights TruNatomy’s conservative shaping capacity, advocating its use in minimally invasive endodontics, whereas ProTaper Next may be reserved for cases requiring aggressive canal preparation.